B. y = 1.09(x - 1) + 1.49
This function rule takes into account that the first pound costs $1.49 and each additional pound costs $1.09. By subtracting 1 from the number of pounds (x-1), we can apply the additional cost of $1.09 for each pound beyond the first. Adding the initial cost of $1.49 gives us the total cost in dollars, y.
The sale price of ground beef at a local grocery store is $1.49 for the first pound and $1.09 for each additional pound. Which function rule shows how the cost of ground beef, y, depends on the number of pounds, x?
A. y = 1.49x + 1.09
B. y = 1.09(x – 1) + 1.49
C. y = (1.09 + 1.49)x
D. y = 1.09x + 1.49
1 answer